Amphiphilic cationic triblock polymers for p53-mediated triple-negative breast cancer gene therapy. (July 2022) - Liu, Hui; Zhao, Xiaoyun; Bai, Yu; Xie, Huichao; Yang, Zhen; Wang, Yichen; Chen, Yongfeng; Luo, Yucen; Ma, Mengrui; Lu, Wenwen; Ma, Jizhuang; Yang, Tianzhi; et al.
Graphical abstract: Highlights: A novel class of amphiphilic triblock cationic polymers were constructed as gene vectors with different physicochemical properties by adjusting hydrophobicity. Amphiphilic vectors increased the interaction of complexes with cell membrane, alleviated the serum inhibition problem commonly seen in cationic vectors. Amphiphilic vectors had a better balance between transfection efficiency and cytotoxicity, and had the potential of application in vivo . The discussion of the structure-activity relationship between amphiphilic and vector properties provided theoretical basis for the optimization of gene vectors. Abstract: Polycationic vectors are a promising class of gene delivery systems. To improve delivery efficiency and reduce cytotoxicity, hydrophobic modification has been proposed as an effective way. Herein, we synthesized a class of terpolymer vectors with various hydrophobicities as well as multiple biodegradable disulfide bonds and cationic side chains. The chemical structure and hydrophobic modification ratio of polymers were characterized. The amphiphilic vectors were able to condense pDNA to form flexible and uniform nanoparticles with a size of 60–85 nm. The shielding effect of hydrophobic side chains led to a lower zeta potential and reduced cytotoxicity. The endocytosis efficiency of amphiphilic vectors was significantly increased and the endocytosis pathway shifted from mainly via the clathrin pathway to clathrin/caveolae/lipid raft co-mediated endocytosis. The amphiphilic vectors demonstrated significantly higher transfection efficiency. In addition, the hydrophobic structural domain of polymers could improve serum stability, alleviating the serum inhibition commonly seen in cationic polymers. Then, we tested the tumor-suppressor gene wtp53 delivered by the amphiphilic vectors in triple-negative breast cancer models both in vitro and in vivo . Tumor cell cycle arrest and apoptosis were triggered through the regulation of downstream cell cycle proteins and apoptosis proteins, inhibiting tumor growth with an excellent safety profile.